Se nourrir dans les rues et sur les chemins de l’Occident musulman (XIIe-XVIIIe siècle) - Bernard Rosenberger (Afriques)
I attempt here to gather informations dating from juridical sources as handbooks of market regulation from xiith to xvith century on a particular kind of foods mostly proposed in the streets of the Muslim towns in Spain and North Africa, and those prepared for travellers.